ШЕКСПИР СОНЕТЛЕРИН ҚАРАҚАЛПАҚ ТИЛИНЕ АЎДАРЫЎДЫҢ АЙРЫМ ЛЕКСИКАЛЫҚ ҲӘМ СТИЛИСТИКАЛЫҚ МӘСЕЛЕЛЕРИ ҲАҚҚЫНДА - Турсынмуратова, З.М. (ILIM hám JÁMIYET, 2023)
The article is devoted to the review of lexical and stylistic features of the translation of Shakespeare's sonnets into the Karakalpak language. The translation of the 130th sonnet, made by M. Karabaev, despite some errors, reveals with sufficient completeness of the parodic-ironic and emotional mood of the Russian original.